2012
DOI: 10.1007/s00011-012-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion

Abstract: These results demonstrate that ROS regulates not only the priming stage, but also the activation stage, of NLRP3 inflammasome activation in LPS + ATP-activated macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 38 publications
5
85
1
Order By: Relevance
“…S100A8/S100A9 heterodimers activate both NF-kB and NLRP3 inflammasome assembly via a NOX/ROS-dependent mechanism. 23,[44][45][46] Intracellularly, S100A8/9 heterodimers serve as a scaffold for the membrane assembly and activation of the NOX complex, 47,48 which generates ROS via transfer of electrons across membranes to generate superoxide. 49 As also shown here, NOX regulates both priming and activation of NLRP3 inflammasomes, including the activation of caspase-1 and IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100A8/S100A9 heterodimers activate both NF-kB and NLRP3 inflammasome assembly via a NOX/ROS-dependent mechanism. 23,[44][45][46] Intracellularly, S100A8/9 heterodimers serve as a scaffold for the membrane assembly and activation of the NOX complex, 47,48 which generates ROS via transfer of electrons across membranes to generate superoxide. 49 As also shown here, NOX regulates both priming and activation of NLRP3 inflammasomes, including the activation of caspase-1 and IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
“…49 As also shown here, NOX regulates both priming and activation of NLRP3 inflammasomes, including the activation of caspase-1 and IL-1b secretion. 44 Moreover, transcription and nuclear localization of b-catenin are redox and NOX1 dependent. 50,51 Although MDSCs are a key paracrine source of S100A9 in the MDS BM microenvironment, 11 we show here that MDS HSPCs also express high intracellular S100A9 across lineages, suggesting that inflammasome activation may be sustained by intracrine DAMP stimulation and, upon cytolysis, reinforce paracrine TLR4 activation and BM MDSC expansion.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Several laboratories, including ours, have shown that QDs can induce excessive ROS formation 38À41 and activation of microglia, 42 and the release of cytokines including interleukin-1β (IL-1β). 43,44 However, these earlier studies did not provide experimental evidence for a mechanistic link between the activation of microglia, lysosomal status, and activation pattern of caspase-1 together with the subsequent release of IL-1β. In the current study, we describe a ratiometric QD-based nanosensor for caspase-1 activity detection.…”
Section: Resultsmentioning
confidence: 93%
“…3,61 In LPS and LPSÀQD treated microglia, we found significantly increased levels of IL-1β as determined by ELISA assays ( Figure 4A). 43 The viability of the cells exposed to LPS and/or LPSÀQD (100 ng/mL and 10 μg/mL) in the presence of serum was within 10% from the control. To determine the activity of caspase-1 which leads to the conversion of pro-IL-1β to IL-1β, we developed and employed a novel nanosensor.…”
Section: Articlementioning
confidence: 87%
See 1 more Smart Citation